Метод выяления факторов риска эмоциональных нарушений для проведения психокоррекции - Рисованая, Л. М. (ХНУРЭ, 2017)
The paper presents a method for identifying the risk factors that cause emotional disorders for psychocorrection. Using the method of correlation pleyades, the relationships between the indices of psychological tests that allow revealing emotional disorders in various groups are analyzed. When developing the method, a mathematical model was obtained for assessing the likelihood of the occurrence of emotional disorders, which made it possible to identify the main signs of emotional disorders in patients with cerebrovascular pathology of chronic form. Using the obtained mathematical model, the signs were identified, when the impact on which psychocorrection is carried out. This method can be useful for psychiatrists, neuropathologists, and for medical psychologists.
Keywords: эмоциональные нарушения; психокоррекция